Prevalence and determinants of dental visits among older adults: findings of a nationally representative longitudinal study - K. Spinler; G. Aarabi; R. Valdez; C. Kofahl; G. Heydecke; H.-H. König; A. Hajek (BMC, 2019)
Abstract Background The first aim was to present descriptive data on the frequency of dental visits among older adults in Germany. The second aim was to identify the determinants of the number of dental visits using a longitudinal approach. Methods Longitudinal data were derived from the German Ageing Survey, which is a nationally representative sample of community-dwelling individuals ≥40 years in Germany. The frequency of dental visits in the past 12 months was recorded in the years 2002, 2008 and 2011. In order to control for time-constant unobserved heterogeneity, Poisson fixed effects regressions were used. Results While the mean number of dental visits was 2.3 (SD: 2.0) in 2002, it was 2.0 (SD: 1.7) in 2008 and 2.1 (SD: 1.7) in 2011. The frequency of dental visits declined with age (total sample and women), transitions from normal weight to overweight (total sample), changes from divorced/widowed/single/married, living separated from spouse to 'married, living together with spouse' in women and with a decrease in the number of physical illnesses (total sample and men). Conclusions The frequency of dental visits declines with age in older adults. While some of the determinants of frequency are non-modifiable (e.g., ageing and worsening of general health), others are modifiable (e.g., change in weight category).